2017
DOI: 10.1080/00380768.2017.1399044
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of alternate wetting and drying (AWD) on methane and nitrous oxide emissions from a paddy field in Thailand

Abstract: Alternate wetting and drying (AWD) is a water-saving irrigation technique in a paddy field that can reduce the emission of methane, a potent greenhouse gas (GHG). It is being adopted to Asian countries, but different results are reported in literatures on methane, nitrous oxide emission, and rice productivity under AWD. Therefore, the local feasibility needs to be investigated before its adoption by farmers. The current study carried out a 3-year experiment in an acid sulfate paddy field in Prachin Buri, Thail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 28 publications
4
44
1
Order By: Relevance
“…It was re-flooded for many times (5 -6 times) with a huge water amount, resulting in the total water use is not much lower than CF. The water use reduction of AWD in this study is very low as compared to other studies (Chidthaisong et al, 2018, Tran et al, 2018 might be due to the soil type and evaporation rate in this study area. The further study to explain the constraints of AWD implementation in each soil type or each area zone should be conducted to recommend the farmers for adoption.…”
Section: Effect Of Biochar Co-applications Combined Awd On Water Usecontrasting
confidence: 74%
See 1 more Smart Citation
“…It was re-flooded for many times (5 -6 times) with a huge water amount, resulting in the total water use is not much lower than CF. The water use reduction of AWD in this study is very low as compared to other studies (Chidthaisong et al, 2018, Tran et al, 2018 might be due to the soil type and evaporation rate in this study area. The further study to explain the constraints of AWD implementation in each soil type or each area zone should be conducted to recommend the farmers for adoption.…”
Section: Effect Of Biochar Co-applications Combined Awd On Water Usecontrasting
confidence: 74%
“…CH4 flux was calculated by using the equation given by Minamikawa et al (2015) that computed from linear regression of the gas concentration increase in the chamber headspace (ppmv) over the sampling time. The seasonal cumulative CH4 emissions were calculated by successive linear interpolation and numerical integration between sampling days, assumed that CH4 emissions on days without the measurement were according to a linear trend (Chidthaisong et al, 2018).…”
Section: Ch4 Emission Measurementmentioning
confidence: 99%
“…In Jakenan, multiple aeration 7 days before the 1st and 2nd N fertilizer topdressing was implemented as AWDS in the first two seasons, and in the succeeding seasons, the threshold of re-flooding changed to 25 cm below the soil surface (Setyanto et al 2018). In Prachin Buri, the plots were re-flooded to 10-cm level under AWDS as compared to 5-cm level under AWD (Chidthaisong et al 2018). In Muñoz, AWDS was implemented as a 7-10-day-long single aeration (i.e., mid-season drainage) in the first two seasons.…”
Section: Data Sourcementioning
confidence: 99%
“…They represent diversified paddy environments in Southeast Asia. Results from each site were reported in separate papers of this issue (Tran et al 2018;Setyanto et al 2018;Chidthaisong et al 2018;Sibayan et al 2018). They monitored the changes in soil carbon (C) content, which may be lost by intensive drainage events, in addition to CH 4 and N 2 O emissions under AWD and CF.…”
Section: Introductionmentioning
confidence: 99%
“…panicle initiation and flowering), in order to promote high levels of grain production and the formation of good quality grain (Price et al, 2013). Numerous studies conducted throughout Asia and parts of North America have demonstrated that AWD can reduce CH 4 emissions by 35–90%, and improve overall water-use efficiency by 35–63% (Chidthaisong et al, 2018; Chu et al, 2015; Linquist Bruce et al, 2014; Rejesus et al, 2011; Setyanto et al, 2018; Tran et al, 2018; Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%